2019
DOI: 10.3390/ijms20071672
|View full text |Cite
|
Sign up to set email alerts
|

Silver and Copper Nanoparticles—An Alternative in Future Mastitis Treatment and Prevention?

Abstract: Nowadays, mastitis is one of the biggest problems in breeding dairy cattle. Treatment of this disease with conventional antibiotics is ineffective because many pathogens are resistant. Researchers have therefore been forced to look for new solutions, and metal nanoparticles (NPs) have been found to be the most appropriate agents. This study uses commercially available silver (AgNPs) and copper (CuNPs) nanoparticles and synthetized silver–copper nanoparticles (AgCuNPs) to evaluate the effect of these NPs on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 38 publications
(59 reference statements)
5
55
0
1
Order By: Relevance
“…Nanoparticle technology is another area that is currently developing as a delivery technique for antimicrobial agents and other drugs (Gomes and Henriques 2016 ). Different types of nanoparticles have already been evaluated for the treatment of mastitis with positive results (Castelani et al 2019 ; Kalińska et al 2019 ; Orellano et al 2019 ; Pinheiro Machado et al 2019 ). Nanoparticle formulations will enhance the uptake of active compound by phagocytes and thereby improving its antibacterial activity (Gruet et al 2001 ).…”
Section: Advances In Treatment Of Mastitismentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle technology is another area that is currently developing as a delivery technique for antimicrobial agents and other drugs (Gomes and Henriques 2016 ). Different types of nanoparticles have already been evaluated for the treatment of mastitis with positive results (Castelani et al 2019 ; Kalińska et al 2019 ; Orellano et al 2019 ; Pinheiro Machado et al 2019 ). Nanoparticle formulations will enhance the uptake of active compound by phagocytes and thereby improving its antibacterial activity (Gruet et al 2001 ).…”
Section: Advances In Treatment Of Mastitismentioning
confidence: 99%
“…Further studies are required to identify the biological effects of nanoparticles. Some of the nanoparticles, like silver and copper nanoparticles (Kalińska et al 2019 ), chitosan nanoparticles (Orellano et al 2019 ), propolis nanoparticles (Pinheiro Machado et al 2019 ) and cationic nisin-lipid nanoparticles (Castelani et al 2019 ) have been reported to show positive results in managing mastitis. The antibiotics that act by inhibiting protein synthesis exhibited significant synergistic effect when used along with silver nanoparticles (Kazemi et al 2014 ).…”
Section: Advances In Treatment Of Mastitismentioning
confidence: 99%
“…Alternatively, antibacterial CuNPs can be used to replace AgNPs for doping TNTs with improved biocompatibility [98,99]. CuNPs are less toxic than AgNPs to human and bovine mammary epithelial cells [344].…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Alternatively, antibacterial CuNPs can be used to replace AgNPs for doping TNTs with improved biocompatibility [98,99]. CuNPs are less toxic than AgNPs to human and bovine mammary epithelial cells [344]. However, it remains a big challenge for chemists and materials scientists to design novel nanomaterials for technological and medical applications utilizing TiO2 NPs and doped TiO2 NPs.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…For example, CuNPs coated with chitosan showed an antibacterial effect comparable to that of traditional oral antimicrobial agents (chlorhexidine and cetylpyridinium chloride) against S. mutans ( Covarrubias et al, 2018 ). In another example, the combination of AgNPs and CuNPs was shown to have a preventive and therapeutic effect in mastitis caused by S. agalactiae ( Kalińska et al, 2019 ).…”
Section: Alternative Antibacterial Therapiesmentioning
confidence: 99%